Erosive polyarthritis in multicentric reticulohistiocytosis mimics rheumatoid arthritis - Suryana, Bagus Putu Putra; Puspitasari, L; Wahono, Cesarius Singgih; Kalim, H (Indonesian Rheumatology Association, 2013)
Multicentric reticulohistiocytosis (MRH) is a very rare multisystemic syndrome.1,2 The first case of MRH was described by Goltz and Layman in 1954 and so far only less than 200 cases have been reported.3-5 It is characterized by the insidious onset of polyarthritis that often evolves into a severe erosive deforming arthritis and characteristic skin lesions composed of nodules and plaques containing lipid-laden (periodic acidSchiff-positive) histiocytes and multinucleated giant cells.6 It most commonly affects the handsand cervical spine.7 MRH is also known as lipoid dermatoarthritis, lipoid rheumatism, and giant cell reticulohistiocytosis.4 MRH is occured due to infiltration of multinucleated giant cells and histiocytes into various tissues. The typical pictures include skin nodules and destructive polyarthritis.3 This entity is frequently mistaken for rheumatoid arthritis (RA).3 MRH is often associated with systemic complication and various types ofmalignancy. Therefore, sometimes it is considered a paraneoplastic syndrome